An Empirical Contribution to the Debate on Corruption,Democracy and Environmental Policy - Lorenzo Pellegrini; Reyer Gerlagh (Fondazione Eni Enrico Mattei (FEEM), 2005)
Both theoretical and empirical studies have shown that democracy and corruption have substantial influence on environmental policy. In this paper, we empirically analyse whether both democracy and corruption are equally important determinants. When these variables are jointly included as explanatory variables, we find that corruption stands out as an important determinant of environmental policies, while democracy has a very limited impact. Further on, we discuss our results in the context of the Environmental Kuznets Curve literature. We argue that institutional disarray that plagues developing countries will make it problematic for them to have increasing environmental policy stringency combined with increasing incomes. Finally, and more optimistically, when we consider our results in the context of institutions and growth, we conclude that there is a possibility of reaching a double dividend. Reductions in corruption would induce both higher growth rates and stricter environmental policies. Thus, institutional improvement is an extremely valuable step in achieving sustainable development.
Keywords: H40; D73; Q56; Q58; 330; Corruption; Democracy; Development; Environmental policy; Institutions; Korruption; Demokratie; Umweltpolitik; Environmental Kuznets Curve; Schätzung; Welt